2006
DOI: 10.1063/1.2200885
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary-field quantum Monte Carlo calculations of molecular systems with a Gaussian basis

Abstract: We extend the recently introduced phaseless auxiliary-field quantum Monte Carlo (QMC) approach to any single-particle basis, and apply it to molecular systems with Gaussian basis sets. QMC methods in general scale favorably with system size, as a low power. A QMC approach with auxiliary fields in principle allows an exact solution of the Schrödinger equation in the chosen basis. However, the well-known sign/phase problem causes the statistical noise to increase exponentially. The phaseless method controls this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
168
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 95 publications
(177 citation statements)
references
References 45 publications
8
168
0
Order By: Relevance
“…Previous studies in a variety of systems have shown that the bias tends to be small, in both models 10,24-27 and realistic materials 13,17,21,23 , making this one of the most accurate many-body approaches for general interacting fermion systems. In this work, we introduce a self-consistent method to further reduce the bias introduced by the constraint from the trial wave function.…”
Section: Self-consistent Methods Coupling With Independent-electromentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in a variety of systems have shown that the bias tends to be small, in both models 10,24-27 and realistic materials 13,17,21,23 , making this one of the most accurate many-body approaches for general interacting fermion systems. In this work, we introduce a self-consistent method to further reduce the bias introduced by the constraint from the trial wave function.…”
Section: Self-consistent Methods Coupling With Independent-electromentioning
confidence: 99%
“…A constraint is applied in some space to restrict the Monte Carlo sampling, which introduces a systematic bias but in turn removes the exponential growth in variance and restores the algebraic complexity of the algorithm. The majority of QMC calculations have employed this approach, including many on spin and fermion models 9,10 , and almost all on realistic systems in condensed matter physics [11][12][13] , nuclear physics 14 , and quantum chemistry [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The auxiliary-field quantum Monte Carlo method has been described elsewhere [2,3]. Here we outline the relevant formulas to facilitate the ensuing discussion.…”
Section: Af Qmc Methodsmentioning
confidence: 99%
“…The Fermion sign/phase problem is controlled approximately according to the overlap of each random walker (Slater determinant) with a trial wave function. Applications of the phaseless AF QMC method to date, including second-row systems [2] and transition metal molecules [13] with planewave basis sets, and first-row [3] and postd [14] molecular systems with Gaussian basis sets, indicate that this often reduces the reliance of the results on the quality of the trial wave function. For example, with single determinant trial wave functions, the calculated total energies at equilibrium geometries in molecules show typical systematic errors of no more than a few milliHartrees compared to exact/experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation